Proyecto de factibilidad para la creación de un burguer en la ciudad de Loja con especialización en hamburguesas al carbón - Romero Rojas, Santiago Xavier (2015)
This paper called “PROJECT FEASIBILITY FOR THE CREATION OF A BURGER IN THE CITY OF LOJA majoring in charbroiled hamburgers " , had as its overall aim is to develop the project to determine the feasibility of creating a burger. The method used were: historical and logical, inductive, deductive, analytical, statistical. To determine the feasibility of the project we address , the market research through field research, scientific research using techniques such as literature , observation and surveys, which allowed them to determine information related to demand, supply and unsatisfied demand. The study results were market; 146,525 potential demand, actual demand 4,295.084; 4,166.231 effective demand. The installed capacity will be 21,600 burgers, but for the first year 80 % was used. The results obtained in the study found that financial need to invest in fixed assets $ 6,136.28 ; Deferred assets $ 2,650.00 and $ 43,379.57 is needed in current assets giving an investment of $ 52,165.85 plus the sales price of each burger for the first year will be 2.87 plus 50 % profit margin was obtained gives the price of $ 4.30. Giving a total revenue of $ 74,285.6. In the profit and loss in the first year of $ 16,417.00 a liquid profit you will be obtained. At the point of balance originates in sales of $ 46,554.82 and an installed capacity of 62.67 % in the first year of production In the financial evaluation, the following results were obtained. The NPV 13,745.10 ; IRR 23.73 % ; PRC , is 2 years 9 months and 3 days; RB / C , is $ 1.50; Sensitivity analysis an increase of 15.60 % in costs and a decrease in income 10.42 was obtained. It is concluded that the project is feasible and should create the burger. Finally, conclusions and recommendations is done according to the results obtained in developing the research project